Association of prediabetes and insulin resistance on prognosis of patients with moderate-to-severe coronary artery calcification: a prospective cohort study - Enmin Xie; Huimin Cai; Zixiang Ye; Min Yang; Lei Feng; Chenggang Zhu; Jia Li; Kefei Dou (Cardiovascular Diabetology)
Abstract Background Prediabetes and insulin resistance are linked to the presence and progression of coronary artery calcification, but their prognostic significance in individuals with moderate-to-severe coronary artery calcification (MSCAC) remains unclear. The triglyceride–glucose (TyG) index, a validated surrogate marker of insulin resistance and a reliable predictor of cardiovascular outcomes, has not been thoroughly investigated for its role in risk stratification in patients with MSCAC. This study sought to evaluate the prognostic value of different prediabetes definitions and to determine whether the TyG index enhances risk stratification in this population. Methods This prospective cohort study consecutively enrolled 4195 patients with angiography-detected MSCAC. Prediabetes was defined using two criteria: the American Diabetes Association (ADA) criteria (fasting plasma glucose [FPG] 5.6–6.9 mmol/L and/or hemoglobin A1c [HbA1c] 5.7–6.4%), and the World Health Organization (WHO)/International Expert Committee (IEC) criteria (FPG 6.1–6.9 mmol/L and/or HbA1c 6.0–6.4%). The primary outcome was the incidence of major adverse cardiovascular events (MACE), including cardiovascular death, nonfatal myocardial infarction, and stroke. Results The prevalence of ADA-defined prediabetes was 36.6%, nearly twice that of WHO/IEC-defined prediabetes (17.9%). Over a median follow-up of 3.1 years, WHO/IEC-defined prediabetes was significantly associated with an increased risk of MACE compared to normoglycemia (adjusted hazard ratio [HR] 1.79, 95% confidence interval [CI] 1.07–2.99), while ADA-defined prediabetes was not. Patients in the highest TyG index tertile had a significantly higher MACE risk than those in the lowest tertile (adjusted HR 2.25, 95% CI 1.30–3.90). Restricted cubic spline analysis demonstrated a positive linear association between the TyG index and MACE risk (P for nonlinearity > 0.05). Notably, individuals with both WHO/IEC-defined prediabetes and a high TyG index had an even higher MACE risk (adjusted HR 2.43, 95% CI 1.12–5.32), whereas those with prediabetes and a low TyG index did not demonstrate a comparable increase (adjusted HR 1.60, 95% CI 0.90–2.85). Incorporating both WHO/IEC-defined glycemic status and the TyG index into the baseline risk model significantly improved its predictive accuracy compared to including either marker alone, as indicated by enhancements in the C-statistic, continuous net reclassification improvement, and integrated discrimination improvement. These findings were consistent in subgroup analyses and sensitivity analyses. Conclusion This study highlights the prognostic value of WHO/IEC-defined prediabetes and the TyG index in identifying high-risk individuals among patients with MSCAC. Integrating these measures into clinical risk assessment may enhance prognostic accuracy and inform more targeted prevention strategies. Graphical abstract